(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Against the background of the COVID-19 pandemic, all countries have recorded an increase in the number of deaths. Special groups of patients were distinguished in which the death rate significantly exceeded the average statistical indicator. One such group includes patients with diabetes mellitus (DM). Many studies conducted in different countries have shown that patients with diabetes have a higher risk of infection with COVID-19, as well as a more severe course of the disease and a higher mortality rate.